Do state and foreign ownership affect investment efficiency? Evidence from privatizations - Chen, Ruiyuan; El Ghoul, Sadok; Guedhami, Omrane; Wang, He (Journal of Corporate Finance, 2017)
Using the high-power setting of newly privatized firms from 64 countries, we examine the relationship between ownership type and firm-level capital allocations as captured by the sensitivity of investment expenditure to investment opportunities. Consistent with our predictions that government and foreign institutional owners are associated with different levels of information asymmetry and agency problems, we find strong and robust evidence that government (foreign) ownership weakens (strengthens) investment-Q sensitivity, thereby increasing investment inefficiency (efficiency). Moreover, we find that the relation between foreign ownership and investment efficiency is stronger when governments relinquish control and country-level governance institutions are weaker. Overall, our findings highlight the important role of ownership type in determining firms' investment behavior and efficiency.